Blastocystis sp. subtype 3 triggers higher proliferation of human colorectal cancer cells, HCT116 - Kumarasamy, V.; Kuppusamy, U.R.; Samudi, C.; Kumar, S. (Springer Verlag (Germany), 2013)
Blastocystis sp. is a commonly found intestinal microorganism and was reported to cause many nonspecific gastrointestinal symptoms. Various subtypes have been previously reported, and the pathogenicity of different subtypes of Blastocystis is unclear and remains as a controversial issue. A recent study has shown that the Blastocystis antigen isolated from an unknown subtype could facilitate the proliferation of colon cancer cells. Current study was conducted to compare the effect of solubilized antigen isolated from five different subtypes of Blastocystis on colon cancer cells, HCT116. A statistically significant proliferation of these cells was observed when exposed to 1.0 Î¼g/ml solubilized antigen isolated from subtype 3 Blastocystis (37.22 , p <0.05). Real-time polymerase chain reaction demonstrated the upregulation of Th2 cytokines especially transforming growth factor beta in subtype 3-treated cancer cells (p <0.01, 3.71-fold difference). Of interest, subtype 3 Blastocystis antigen also caused a significantly higher upregulation of cathepsin B (subtypes 1 and 2, p <0.01; subtypes 4 and 5, p <0.001; 6.71-fold difference) which lead to the postulation that it may enhance the exacerbation of existing colon cancer cells by weakening the cellular immune response. The dysregulation of IFN-Î³ and p53 expression also suggest Blastocystis as a proponent of carcinogenesis. Therefore, it is very likely for subtype 3 Blastocystis to have higher pathogenic potential as it caused an increased propagation of cancer cells and substantial amount of inflammatory reaction compared to other subtypes.